Effectiveness of Quinacrine (Mepacrine) in Photosensitive Autoimmune Diseases, Lupus Erythematosus, and Dermatomyositis: Report on 38 Cases and Literature Review - Raquel RIOS-FERNÁNDEZ,; Jose-luis CALLEJAS-RUBIO,; Norberto ORTEGO-CENTENO, (Archives of Rheumatology, 2019)
Objectives: This study aims to report our experience with photosensitive autoimmune diseases including lupus erythematosus and dermatomyositis (DM) treated with quinacrine (Qn) as either monotherapy or combination with other antimalarials, steroids, and immunosuppressive therapy in an add-on regimen in light of a review of the relevant literature. Patients and methods: The study included 38 patients (6 males, 32 females; mean age 45±8 years; range, 23 to 72 years) with systemic lupus erythematosus (SLE), cutaneous lupus or DM who had been treated with Qn. The following data were obtained from the records of each patient: sex, age, diagnosis, duration of the disease, duration of treatment, smoking behavior, antimalarial treatment, concomitant treatment, and clinical indications, as well as Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) and Cutaneous Lupus Erythematosus Disease Area and Severity Index (CLASI) activity before initiation, at the last visit, or when Qn treatment was completed. We carried out a MEDLINE search for previously reported cases that, together with our patients, served as the basis of this report. Results: Of the 38 patients, 34 were suffering from SLE or cutaneous lupus and four from DM. Qn was dosed at 50 or 100 mg in most of the patients. Twenty-seven patients received Qn as an add-on regimen therapy. Clinical response was analyzed in patients with SLE or cutaneous lupus. Of the patients, 25 responded (68.4%), 13 (52%) had improved CLASI activity and 12 (48%) had improved SLEDAI score. Fifty percent of the patients with DM responded. A total of 188 cases were identified from the literature. The most frequent diagnosis was cutaneous lupus (68.6%), followed by SLE (32.6%). Only 7.4% of the patients had DM. The majority of the patients received concomitant immunosuppressive medications. Treatment response was 73% in patients with SLE and/or cutaneous lupus and 35.7% in patients with DM. Side effects were scarce and the most frequent was yellow skin discoloration. Conclusion: Quinacrine may be an alternative for patients with poor response or those who are intolerant to other antimalarials. Thus, Qn may aid in controlling the activity of photosensitive autoimmune diseases.